Analysis of physical activity of gross motor movements in early childhood : Systematic literature review - Faizah, Khairani; Sumaryanti, Sumaryanti; Sulistiyono, Sulistiyono; Alim, Abdul (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2024)
Early childhood naturally experiences gross motor movement development which is important for their motor and cognitive abilities. In this literature review, we investigated the relationship between physical activity and gross motor movement development in early childhood. We conduct systematic searches in leading scientific databases and analyze relevant studies. Our findings suggest a significant positive association between participation in structured physical activity and gross motor movement development in early childhood. Activities such as play, sports, and gymnastics programs are designed to improve coordination, muscle strength, and other gross motor skills. However, there is a lack of in-depth research in this context, especially in terms of methodology and consistent measurement. Therefore, this review highlights the need for more in-depth follow-up research to better understand the relationship between physical activity and gross motor movement development in early childhood. The implications of this study may aid in the development of more effective intervention programs to improve gross motor skills in early childhood